2007
DOI: 10.1007/s00127-007-0207-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social justice, long-term unemployment and health

Abstract: While this study does not allow to establish causal relationships, the associations we found suggest that also perceived social justice needs to be taken into account in interventions that are intended to foster equity in health among socially disadvantaged groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…social integration or emotional support) and internal health resources (e.g. health locus of control or sense of coherence) [14,15]. For CVD, not only the classical risk factors hypertension, dyslipidemia, diabetes mellitus, obesity, and smoking [16,17], or lifestyle associated risk factors like a calorie-rich diet with low intake of fruits and vegetables, and lack of exercise [7] have been identified as independent risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…social integration or emotional support) and internal health resources (e.g. health locus of control or sense of coherence) [14,15]. For CVD, not only the classical risk factors hypertension, dyslipidemia, diabetes mellitus, obesity, and smoking [16,17], or lifestyle associated risk factors like a calorie-rich diet with low intake of fruits and vegetables, and lack of exercise [7] have been identified as independent risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The health related unemployed appear especially vulnerable to the negative effects of unemployment due to additional loss of life/social structure, personal purpose and work identity (Bennett, 1970;Grove, 2006). Length of time unemployed is associated with deteriorating psychological health (Freidl, Fazekas, Rami, Pretis & Feistritzer, 2007), physical de-conditioning (Waisak, Verma, Pransky & Webster, 2004) and ongoing financial strain (Price, Choi & Vinokur, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently migrants would refrain from consulting medical doctors because of their illegal status and for the fear of being criminalized [3][4][5][6][7]. Research has shown that in many countries migrants and marginal groups have poorer health than the local populations [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%